1997
DOI: 10.1038/sj.onc.1201380
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAP kinase activation by vascular endothelial growth factor mediates actin reorganization and cell migration in human endothelial cells

Abstract: Vascular endothelial growth factor (VEGF) is a potent chemotactic agent for endothelial cells. Yet the signalling pathways that modulate the motogenic effects of VEGF in vascular endothelial cells are still ill defined. In the present study, we found in primary cultures of human umbilical vein endothelial cells (HUVEC) that VEGF increased cell migration and induced a marked reorganization of the microfilament network that was characterized by the formation of stress fibers and the recruitment of vinculin to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
640
5
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(685 citation statements)
references
References 29 publications
39
640
5
1
Order By: Relevance
“…Thus, we concluded that ERK is essential for DNA synthesis and that p38 MAP kinase is essential for cell migration. The involvement of p38 MAP kinase in the migration of endothelial cells has recently been suggested for VEGF as well [36]. The activation of ERK and p38 MAP kinase in response to S1P was also inhibited by PTX, suggesting that both ERK and p38 MAP kinase may be located downstream of the G i \G o -proteins in S1P signalling.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, we concluded that ERK is essential for DNA synthesis and that p38 MAP kinase is essential for cell migration. The involvement of p38 MAP kinase in the migration of endothelial cells has recently been suggested for VEGF as well [36]. The activation of ERK and p38 MAP kinase in response to S1P was also inhibited by PTX, suggesting that both ERK and p38 MAP kinase may be located downstream of the G i \G o -proteins in S1P signalling.…”
Section: Discussionmentioning
confidence: 80%
“…Inhibition of p38 MAPK augments VEGFinduced angiogenesis in the chicken chorioallantoic membrane (CAM) assay (Issbrucker et al, 2003;, without an accompanying increase in vascular permeability (Issbrucker et al, 2003). Moreover, p38 MAPK induces phosphorylation of heat-shock protein-27 (HSP27), a molecular chaperone that positively regulates VEGFinduced actin reorganization and migration (McMullen et al, 2005;Rousseau et al, 1997).…”
Section: Vegf Signalingmentioning
confidence: 99%
“…However, VEGFinduced activation of VEGFR2 also activates the serine/threonine protein kinase p38 MAPK (Rousseau et al, 1997). This kinase is an important modulator of the pro-apoptotic process in various cell types, including endothelial cells.…”
Section: Vegf and Cellmentioning
confidence: 99%
“…18 p38 MAP kinase activation by VEGF mediates actin reorganization and cell migration in human endothelial cells. 19 By modulating cell migration, p38 may thus be an important regulator of angiogenesis.…”
Section: Genes Related To Extracellular Matrixmentioning
confidence: 99%